THE INFLUENCE OF SOCIAL MEDIA ON INTEREST TO BUY ONLINE (CASE STUDY OF STIE BIMA STUDENTS) - purnamasari, Esti; Ismunandar, Ismunandar (Jurnal Ekonomi Balance, 2020)
This study aims to determine the effect of social media on online buying interest (case studies on senior students) with 50 respondents. The indicators of social media (x) consist of 2 namely trust and convenience while the indicators of buying interest (y) consist of 4 namely transactional interest, refrential interest, preferential interest and explorative interest. The definition of this study uses 2 variables: the independent variable is social media (x) and the dependent variable is online buying interest (y). The research method is an associative research using a qualitative approach consisting of questionnaire data. Data analysis techniques used in this study are validity, reliability, simple linear regression, simple correlation coefficient, correlation, coefficient of determination and using the statistical t test. The results showed that the influence of social media significantly influenced online buying interest.